Effectiveness and safety of serial endoscopic ultrasound–guided celiac plexus block for chronic pancreatitis - Sey, Michael S. L.; Schmaltz, Leslie; Al-Haddad, Mohammad A.; DeWitt, John M.; Calley, Cynthia S. J.; Juan, Michelle; Lasisi, Femi; Sherman, Stuart; McHenry, Lee; Imperiale, Thomas F.; LeBlanc, Julia K. (Endoscopy International Open, 2015)
Background and study aims: Endoscopic ultrasound – guided celiac plexus block (EUS-CPB) is an established treatment for pain in patients with chronic pancreatitis (CP), but the effectiveness and safety of repeated procedures are unknown. Our objective is to report our experience of repeated EUS-CPB procedures within a single patient. Patients and methods: A prospectively maintained EUS database was retrospectively analyzed to identify patients who had undergone more than one EUS-CPB procedure over a 17-year period. The main outcome measures included number of EUS-CPB procedures for each patient, self-reported pain relief, duration of pain relief, and procedure-related adverse events. Results: A total of 248 patients underwent more than one EUS-CPB procedure and were included in our study. Patients with known or suspected CP (N = 248) underwent a mean (SD) of 3.1 (1.6) EUS-CPB procedures. In 76 % of the patients with CP, the median (range) duration of the response to the first EUS-CPB procedure was 10 (1 – 54) weeks. Lack of pain relief after the initial EUS-CPB was associated with failure of the next EUS-CPB (OR 0.17, 95 %CI 0.06 – 0.54). Older age at first EUS-CPB and pain relief after the first EUS-CPB were significantly associated with pain relief after subsequent blocks (P = 0.026 and P = 0.002, respectively). Adverse events included peri-procedural hypoxia (n = 2) and hypotension (n = 1) and post-procedural orthostasis (n = 2) and diarrhea (n = 4). No major adverse events occurred.Conclusions: Repeated EUS-CPB procedures in a single patient appear to be safe. Response to the first EUS-CPB is associated with response to subsequent blocks.